PHYSIOLOGICAL FUNCTIONS OF THE HEART AND THEIR PATHOLOGICAL ALTERATIONS: CLINICAL SIGNIFICANCE AND DIAGNOSTIC OPPORTUNITIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cardiovascular diseases remain the leading cause of mortality worldwide and represent one of the most pressing global public health challenges of the 21st century. The heart, being the central organ of circulation, is responsible for ensuring tissue oxygenation, maintaining systemic homeostasis, and supporting adaptive responses during both rest and stress. A deep understanding of the physiological functions of the heart and the pathological alterations that disrupt these mechanisms is crucial for the early detection, accurate diagnosis, and targeted treatment of cardiovascular diseases. Advances in modern medicine demand a comprehensive analysis of cardiac physiology and pathology to reduce the burden of morbidity and mortality associated with these disorders.